Penyerapan Tenaga Kerja Provinsi Kalimantan Tengah dan Faktor-Faktor yang Mempengaruhinya - Sugiharto, Sigit Dwi; , Muhammad Arif, SE, M.Ec, Dev (2017)
This Study Entitled "Employment in Central Kalimantan Province and The Factors that Influence" as for the purpose of analyzing the effect of the production value of the number of business units and the minimum wage on employment investment of small and medium industries in the Province of Central Kalimantan from the years 2011-2015. The dependent variable in the form of Employment (TK), while the dependent variabel such as the value of production (Q), the number of business units (COMP), regional minimum wage (UMR) and investment (INV) research using secondary data with panel data regression analysis techniques The results showed that the fixed Effects model (FEM) is a panel data gression model is most appropriate. Based on test validity or the effect of the t test, two variabel regional minimum wages and the value of production significantly and negatively, while the two other variables, namely the number of business units and investments positive and significant impact on employment on small and medium industries in theProvince of central Kalimantan. Keyword : value of production, the number of business, regional minimum wage, investment, and Employment.